The Great Cistercian Mystics: A History - McGinn, Bernard (Crossroad Publishing Company, 2018)
The Great Cistercian Mystics is an in-depth analysis of the mystical theology of the major Cistercian mystics of the 12th century, Bernard of Clairvaux, William of Saint-Thierry, Guerric of Igny, Isaac of Stella, and Aelred of Rievaulx, as well as the continuators of Bernard's sermons on the Song of Songs. It also contains a survey of the Cistercian women mystics of the 13th century.
Keywords: Body, Mind & Spirit / Mysticism; Religion / Mysticism; Religion / Spirituality